Patient and public involvement in the SPRUCE methodology study investigating electronic patient reported outcomes in oncology clinical trials - Morgaine Stiles; Monisha Dewan; Georgina Manning; Jessica Maudsley; Diana King; Jacqui Gath; Andy Deutsch; Esme Radin; Kim Watson; Franko Kowalczuk; Stephanie Foster; Alexa Gillman; et al. (Research Involvement and Engagement)
Abstract Background Patient reported outcomes (PRO) provide crucial insight into trial participants’ experience of oncology treatments. At the Clinical Trials and Statistics Unit at the Institute of Cancer Research (ICR-CTSU), these are completed by participants on paper. The SPRUCE study within a trial (SWAT) investigates the impact of PRO questionnaire modality (paper or electronic) on the data received. To ensure SPRUCE is acceptable and appropriately patient-focused, we involved Patient and Public Involvement (PPI) partners throughout development and oversight. Body A survey was developed with PPI input, to assess public attitudes to electronic completion of healthcare questionnaires. We advertised in local papers to reach respondents without internet access; other avenues were limited due to the COVID-19 pandemic. Survey respondents were invited to virtual discussion groups to review the proposed SWAT design and provide feedback on its relevance and acceptability to potential study participants. Discussion group contributors were invited to join the SPRUCE Patient and Public Oversight Committee, providing PPI input throughout the study. Committee members were given a document explaining clinical trials, the SPRUCE study, and the committee itself. The first committee meeting saw PPI members testing the electronic PRO (ePRO) system and giving feedback on this and the patient-facing documents, for which we provided structured feedback forms. Members also provided feedback on the meeting itself. Of the fifty survey respondents, eight joined a discussion group. Six subsequently joined the Patient and Public Oversight Committee, along with one patient advocate who had been involved in the initial study design and funding application. Each committee member had access to the internet and would prefer to complete PRO questionnaires electronically. Six committee members tested the online ePRO completion system using various personal devices, resulting in changes including the addition of a free text box for participants to leave comments. Patient and public input also shaped patient-facing study documentation, including wording of the patient information sheet and correspondence to participants. Conclusions Despite challenges faced in accessing a diverse demographic, PPI input has improved SPRUCE by ensuring the patient viewpoint is central to study oversight, helping identify ways to improve participant experience and streamlining study processes.